Penguatan Kesadaran Lingkungan Masyarakat melalui Edukasi Pengelolaan Sampah Berbasis 3R di Kecamatan Ampana - Nurhikmah Supardi; Zeffitni Zeffitni; Martini Martini; Abdul Mukaddas; Ajeng Listianti; Apriadi Saputra; Deno Ambar Arum (Universitas Negeri Gorontalo, 2026)
The increasing volume of household waste and the low level of public awareness regarding waste management have become environmental problems in Ampana District. This community service activity aimed to improve community knowledge and awareness in managing household waste through the application of the 3R principles (Reduce, Reuse, Recycle). The program involved 45 participants consisting of community members and local officials. The activity was conducted using a participatory counseling approach through interactive lectures, group discussions, and demonstrations of recycled products. The implementation stages included preparation through field observation and coordination with stakeholders, program implementation using pretest and counseling sessions, and evaluation through posttest questionnaires to measure changes in participants’ knowledge and behavior. The results showed that participants’ knowledge regarding waste management increased from 55% to 90%, while household waste sorting behavior increased from 40% to 87%. These findings indicate that 3R-based counseling was effective, within the scope of this activity, in improving environmental awareness and encouraging community participation in sustainable waste management. In addition, the activity opened opportunities for the development of community-based recycling initiatives such as waste banks and household-scale recycling businesses.